(untitled) (Nonconventional Technologies Review, 2019)
The paper is focuses to establish the principal setting parameter for the 3D printing DLP (Digital Light Processing) process, which have an influence on the surface characteristics of the flat or round parts. In the first part of the paper are analyzed the principal value parameter which may have a relevant influence for the printing of the 3D plane surfaces for the DLP process. This method was chosen because a relative reduce costs of generating planar surface for objects occurs, but also for the generation mode is relatively simple from a technological point of view. The printer and the program used for generation is presented, which both constructively and functionally will be analyzed, both as functionality and as component design possibilities. Next chapter allocated to the ordering of technological parameters of 3D generation by printing the parts with define the main technological generation parameters of the parts with statistically ordering data. This step is important to ensure the assembly conditions of the components, and also to the fact that the materials used to make the parts produce different behavior after the three directions in terms of contractions and the dimensions variation. In the last chapter are presented some of the domain specific elements generated by 3D printing with DLP are used. Surface analysis will be done both by optical and dimensional measurement of surface. The dimensional measurement of the part made with digital measuring devices and optical method. The paper also refers to the generating methodology of flat or round surfaces and the influence on the characteristics of the generated parts. It is apparent from point of view of the areas generated literature there are few references in this direction.